Diseases of the circulatory system: health status and perspectives for changes - V. I. Klimenko; A. V. Kovalenko (Zaporožskij Medicinskij Žurnal)
During last 20 years rates of incidence and prevalence of diseases of the circulatory system in Ukraine have been growing from year to year and became problems of current interest. According to the program of WHO, realization of diseases prevention is provided by using of scientific justification and monitoring of health indexes, including diseases of the circulatory system.